Jezebel unhinged: loosing the black female body in religion and culture - Lomax, Tamura A. (Duke University Press, 2018)
Prolegomenon: "hoeism or whatever": Black girls and the sable letter "b" -- Introduction: "a thousand details, anecdotes, stories": mining the discourse on Black womanhood -- Black Venus and Jezebel sluts: writing race, sex, and gender in religion and culture -- "These hos ain't loyal": white perversions, Black possessions -- Theologizing Jezebel: womanist cultural criticism, a divine intervention -- "Changing the letter": toward a Black feminist study of religion -- The Black church, the Black lady, and Jezebel: the cultural production of feminine-ism -- Whose "woman" is this?: reading Bishop T.D. Jakes's Woman, Thou Art Loosed! -- Tyler Perry's new revival: Black sexual politics, Black popular religion, and an American icon -- Epilogue: dangerous machinations: Black feminists taught us